Guardianship of a child's property: rights of the child v. responsibilities of the guardian - Halim, Akmal Hidayah; Ahmad Bustami, Tajul Aris (2010)

(untitled)
Guardianship is a management by an adult of a child and his property. The guardianship of a child's property becomes an issue where the child acquires significant assets particularly through inheritance. The guardianship expires upon the child reaching the age of majority unless for reasons of insanity or other disability, the child remains unable to take care of himself or to manage his property. The guardian is responsible for managing the child’s property honestly and in his best interests, using it to pay for normal living expenses, health and education. A guardian is a fiduciary and is subject to a very high standard of care in exercising his powers. However, there are cases where the guardian fails to discharge his duties accordingly and wastes or mismanages the child’s property causing financial loss to the latter’s property. Hence, this paper will focus on the guardianship of a child’s property giving emphasis on the rights of a child to inheritance and the guardianship over his property throughout his minority. The administration of the property by the guardian will be highlighted to examine the scope of the guardian’s duties and the extent of his responsibilities in managing the property. The rights of the child against the unlawful acts of the guardian will also be analyzed so that the child’s rights are legally ascertained and protected.